1994
DOI: 10.1159/000147620
|View full text |Cite
|
Sign up to set email alerts
|

The Carbohydrate Epitope 3-Fucosyl-N-Acetyllactosamine Is Region-Specifically Expressed in Astrocytes of the Rat Brain

Abstract: The carbohydrate epitope 3-fucosyl-N-acetyllactosamine (CD 15) is involved in cell-to-cell recognition processes in various tissues. In the CNS of the adult rat, immunoreactivity for CD 15 reveals a region-specific distribution pattern by light microscopy. In the present study we investigated the ultrastructural localization of CD 15 in the rat brain using preembedding immunocytochemical methods. In addition we studied CD 15 expression in cultured astrocytes from optic nerves of 11-day-old rats. In optic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Results obtained for P5 and P9 were essentially the same (data not shown). Results obtained for P9 and P32 are shown in Figure 2 and support those of previous studies on CD15 and HNK-1 on rat postnatal cerebellum (reviewed by Gocht, 1994;Jungalwala, 1994). At P9, it is apparent that CD15 and HNK-1 are present on different cell populations.…”
Section: Cd15 Is Expressed On a Subset Of Cells In The Developing Possupporting
confidence: 87%
See 4 more Smart Citations
“…Results obtained for P5 and P9 were essentially the same (data not shown). Results obtained for P9 and P32 are shown in Figure 2 and support those of previous studies on CD15 and HNK-1 on rat postnatal cerebellum (reviewed by Gocht, 1994;Jungalwala, 1994). At P9, it is apparent that CD15 and HNK-1 are present on different cell populations.…”
Section: Cd15 Is Expressed On a Subset Of Cells In The Developing Possupporting
confidence: 87%
“…The CD15 staining is clustered around the developing Purkinje cells and their dendrites, resulting in a particulate, densely stained molecular layer. Gocht et al (1994) have previously demonstrated by electron microscopy studies that the CD15 in the molecular layer is localized to the glial cell surface. As the Bergmann glial fibers emerge into the external granule cell layer, where no dendrite ensheathing is occurring, the CD15 staining is visualized more clearly as straight, stained fibers.…”
Section: Cd15 Is Expressed On a Subset Of Cells In The Developing Posmentioning
confidence: 95%
See 3 more Smart Citations